The Disappearing Audience and Reflexive Visibility - Girginova, Katerina (Social Media + Society, 2016)
Contrary to popular opinion and some academic writing that celebrates the renewed visibility of new media audiences, this essay argues that they are increasingly going into retreat. To understand how new media audiences “disappear” from view of one another, I borrow from Brighenti’s typology of visibility and develop the idea of “reflexive visibility.” The latter describes the ability to socially orient ourselves in a digital environment through the textual and contextual cues of others—an activity that is of utmost importance not only to researchers wishing to “see” various audiences but also for audiences writ large, wishing to know themselves.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMDU2MzA1MTE2NjYyMTcy